Behavioural organisational factors affecting strategic management practice in urban councils in Zimbabwe - Edward Chinongwa Edward (Universitas Kuningan, 2023)
The study sought to explore behavioural organisational factors affecting strategic management practice in urban councils in Zimbabwe. A quantitative research approach was adopted in the study with a population of 3031. A cluster sampling technique was adopted where a sample size of 341 professional employees were selected, using the Krejcie Morgan sample size determination table. A questionnaire was adopted in the collection of data after a pilot study and internal consistency was used to test for reliability, where Cronbachâ€™s Alpha co-efficient of above 0.7 confirmed the reliability of the research instrument. SPSS version 23 was used in the analysis of data. Descriptive statistical techniques which involve mean, standard deviation, frequency and percentages were used in the data analysis. Organisational culture, organisational structure and technology innovativeness capability were used as variables for assessment. From the findings, it emerged that organisational culture, organisational structure and technology innovativeness capability have a significant influence in the practice of strategic management in urban councils in Zimbabwe.Key words: behavioural factors, organisational culture, organisational structure, strategic management, technology innovativeness capability Â